Reconstructing distribution of the Eastern Rock Nuthatch during the Last Glacial Maximum and Last Interglacial. Issue 1 (May 2020) - Yousefi, Masoud; Shabani, Afshin Alizadeh; Azarnivand, Hossein
Species distribution models have many applications in ecology, conservation, biogeography, and even paleoecology. In this study, we modeled the distribution of the Eastern Rock Nuthatch ( Sitta tephronota ), a common rock dweller bird in Iranian Plateau, and determined most important climatic variables affecting the distribution of the species. We then projected the species distribution into the past, the Last Glacial Maximum (21, 000 yr BP) and Last Interglacial (~120, 000– 140, 000 yr BP), to investigate how the species' range would have changed through time. Results indicated that Zagros Mountains, Alborz Mountains and Kopet Dagh Mountains in the northeast of Iran are the most suitable habitats for the Eastern Rock Nuthatch. Annual mean temperature and annual precipitation identified as the most important variables in predicting the distribution of this species. During the Last Glacial Maximum, potential distribution of Eastern Rock Nuthatch was larger from its current distribution; however, the species' climatic niche remains relatively stable since the Last Glacial Maximum. Our results also showed that during the Last Interglacial, distribution of the Eastern Rock Nuthatch was restricted to high elevations and was very different compared to its current distribution.